Preparation and characterization of polyethylene octene grafted maleic anhydride toughened polyamide 6/ polypropylene nanocomposites [compact disc] - Norhayani Othman 249191 (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2006